(untitled) (Bangladesh Journal of Bioethics, 2019)
Psychotherapists and counsellors confront several ethical dilemmas as they tend to provide effective services. There has been much debate among psychotherapists and counsellors alike around the utility of therapeutic contracts. Some view contracts as being restrictive to the therapeutic process and often hindering the work done in sessions. In contrast, many counsellors and psychotherapists use those agreements to revisit specific therapeutic topics and establish the guidelines necessary for this professional arrangement. No matter the opinion or preference of contracts, the development of written and/or verbal consent of specific topics in psychotherapy remains essential. This remains one of the formal features of the arrangement and starting relationship in current counselling and psychotherapy practice. This paper aims to discuss the necessity and ethical demand of therapeutic contract in counselling and psychotherapy practice.